Crawford Tube Stenting after Failed Medical Treatment and Failed Probing in Patients with Congenital Nasolacrimal Duct Obstruction (Medical Forum Monthly, 2021)
Objective: Assess reduction in post-operative symptoms after Crawford tube stenting in patients with congenital nasolacrimal duct obstruction (CNLD)Study Design: Experimental / longitudinal studyPlace and Duration of Study: This study was conducted at the Isra postgraduate institute of Ophthalmology, Al-Ibrahim eye hospital Karachi from January-2020 to December-2020Materials and Methods: After seeking approval, a longitudinal study was conducted in which 103 patients aged 1-5 years with CNLDO were selected. In all the patients probing was carried out. After probing, a Crawford tube stent was inserted through the upper and lower punctum with the probes removed and the free ends tied to the nose. Data was analyzed using SPSS Version 21.0. Post stratification, Chi-square/Fisher exact test will be applied to assess significant association between success of the treatment. P-value<0.05 will be considered significant.Results: 103 patients were included in the study, 70 (68.6%) male and 33 (31.4%) female with the mean age of patients being 3.1±1.7 years. No significant difference was seen in the 1st week and 1st month regarding discharge and regurgitation test (P=0.310, P=0.555). However, significant difference was seen in the 3rd month after treatment (P≤0.000).Conclusion: Crawford tube stenting is an effective procedure after medical and probing has failed in patients with congenital nasolacrimal duct obstruction.